THE PROBLEM OF GENRE DIFFERENTIATION: CLASSIC DETECTIVE STORY AND A POLICE NOVEL - Khaydarova Umida Pulatovna (Web of Journals Publishing, 2024)
The article highlights the main distinguishing features of the two leading criminal genres, which are most often mixed with each other: the detective (in its classical version) and the police novel. The readers' attention is offered a comparative table, clearly showing the similarities and differences in the poetics of these genres. While these genres have distinct characteristics, there are instances where elements overlap. Some novels may feature a detective working closely with a police team, blurring the lines between the two genres. Additionally, certain authors and series have successfully combined elements of both classic detective stories and police procedurals in their works.
Keywords: criminal genres; classic detective; police novel, investigator, motives.